Perception of nasal reduction by radix and tip augmentation rhinoplasty - Eduardo Antonio Torres Furlani; José Glauco Lobo Filho; Fábio Rocha Fernandes Távora (Revista Brasileira de Cirurgia Plástica, 2018)
INTRODUCTION: A straight bridge has always been the aesthetic ideal. Simple hump removal, the classical and most commonly applied method, can have aesthetic and functional consequences. However, great resistance to augmentation procedures persists because most patients request reduction and the benefits of improving nasal balance are counterintuitive. An augmented nose can look smaller, a particular benefit in patients with thick, inelastic skin or a large lower nose. On the other hand, decreased size perception after raising of the radix and tip is very common but has not been measured to date. METHODS: This study created graphic and real interventions to achieve a straight bridge through radix and tip raising and analyzed how patients and independent observers perceive these changes. A sample of 42 sequential rhinoplasty patients was analyzed, including nine cases of primary surgery and dorsal convexity. RESULTS: There was a 6.5% mean augmentation after graphic computing intervention but a perception of size reduction (p = 0.004). There was a 1% mean augmentation after rhinoplasty and an overall size reduction perception. CONCLUSION: Correction of the nasal dorsum, making a straight bridge through slightly increasing radix and tip, creates the perception of a decreased nose size.